2010
DOI: 10.1517/13543780903563372
|View full text |Cite
|
Sign up to set email alerts
|

Investigational therapies for non-muscle invasive bladder cancer

Abstract: Despite recent enthusiasm for novel agents, radical cystectomy remains the treatment of choice for patients with NMIBC who have failed intravesical therapy. However, evidence is accumulating that novel agents provide an efficacious alternative in patients refractory or intolerable to BCG or unfit for cystectomy. Further randomized prospective data are required to demonstrate a recurrence- and progression-free benefit compared with BCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(52 citation statements)
references
References 99 publications
0
52
0
Order By: Relevance
“…26,27 Concern regarding BCG-related toxicity and disease progression has led to the study of other intravesical chemotherapeutic agents (Table 1) in the treatment of NMIBC, most notably mitomycin C (MMC). 9 However, large meta-analyses examining patients with Ta and T1 TCC have concluded that BCG is superior to intravesical chemotherapy in preventing tumor recurrence in patients at high risk 28,29 and when maintenance therapy is utilized. 17,30 Sylvester et al reviewed nine randomized trials including 700 patients with CIS treated with either BCG or intravesical chemotherapy (MMC, epirubicin, adriamycin, or combination therapy).…”
Section: Bacillus Calmette-guerinmentioning
confidence: 99%
See 4 more Smart Citations
“…26,27 Concern regarding BCG-related toxicity and disease progression has led to the study of other intravesical chemotherapeutic agents (Table 1) in the treatment of NMIBC, most notably mitomycin C (MMC). 9 However, large meta-analyses examining patients with Ta and T1 TCC have concluded that BCG is superior to intravesical chemotherapy in preventing tumor recurrence in patients at high risk 28,29 and when maintenance therapy is utilized. 17,30 Sylvester et al reviewed nine randomized trials including 700 patients with CIS treated with either BCG or intravesical chemotherapy (MMC, epirubicin, adriamycin, or combination therapy).…”
Section: Bacillus Calmette-guerinmentioning
confidence: 99%
“…31 Further review of these analyses has led to the current American Urological Association (AUA) consensus that an induction course of BCG followed by maintenance therapy is recommended for the treatment of high-grade Ta or T1 TCC and CIS. 6,7,9 Although currently first-line therapy for high-risk NMIBC, five-year recurrence rates are estimated to be 34% in patients receiving BCG maintenance therapy. 7 The efficacy of BCG is also hampered by side effects and treatment intolerance, as well as the risks of understaging or progression to muscle-invasive disease.…”
Section: Bacillus Calmette-guerinmentioning
confidence: 99%
See 3 more Smart Citations